TLR4-mediated AKT Activation is MyD88/TRIF-dependent and Critical for Induction of OxPhos and Mitochondrial Transcription Factor A in Murine Macrophages - Bauerfeld, Christian P. (2012)
Mitochondria play a critical role in cell survival and death. Mitochondrial recovery during inflammatory processes such as sepsis is associated with cell survival. Recovery of cellular respiration, mitochondrial biogenesis and function requires coordinated expression of transcription factors encoded by nuclear and mitochondrial genes, including mitochondrial transcription factor A (T-fam) and cytochrome c oxidase (COX, complex IV). LPS elicits strong host defenses in mammals with pronounced inflammatory responses but also triggers activation of survival pathways such as AKT pathway. AKT/PKB is a serine/threonine protein kinase playing an important role in cell survival, protein synthesis, and controlled inflammation in response to TLRs. Hence, we investigated the role of LPS mediated AKT activation in mitochondrial bioenergetics and function in cultured murine macrophages (B6-MCL) and bone marrow derived macrophages. We show that LPS challenge led to increased expression of T-fam and COX subunit I and IV in a time dependent manner through early phosphorylation of the PI3kinase/AKT pathway. PI3K/AKT pathway inhibitors abrogated LPS mediated T-fam and COX induction. Lack of induction was associated with decreased ATP production, increased proinflammatory cytokines (TNF-α), nitric oxide production and cell death. The TLR4 mediated AKT activation and mitochondrial biogenesis required activation of adaptor protein MyD88 and Toll-IL-1R-containing adaptor inducing IFN-β (TRIF). Importantly, using a genetic approach, we show that the AKT1 isoform is pivotal in regulating mitochondrial biogenesis in response to TLR4 agonist.